1995
DOI: 10.1093/ajcp/104.4.375
|View full text |Cite
|
Sign up to set email alerts
|

p53 Protein Expression and p53 Gene Mutation in Thymic Epithelial Tumors:An Immunohistochemical and DNA Sequencing Study

Abstract: p53 protein expression in 34 thymic epithelial tumors was examined immunohistochemically, and p53 gene mutation was detected in selected cases by DNA sequencing, using formalin-fixed and paraffin-embedded tissues. The tumors comprised 12 noninvasive thymomas, 9 invasive/metastatic thymomas, and 13 thymic carcinomas. All the tumors were immunoreactive for p53 protein. The p53-positive tumor cells in noninvasive thymoma were less than 10% (low expressor) in 7 cases and 10% to 50% (moderate expressor) in 5 cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 26 publications
8
33
1
Order By: Relevance
“…Many studies concerning the expression of p53 protein, bcl-2, and matrix metalloproteinases, counts of argyrophilic nucleolar organizer regions and proliferating cell nuclear antigen, and the Ki-67 index [22][23][24][25][26][27][28] have been conducted to predict the biological behavior of thymomas. In the present study, because we found D2-40 immunoreactivity in metastatic tumor cells within the lymph nodes, we hypothesized that podoplanin expression could be a useful marker of more aggressive behavior of thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies concerning the expression of p53 protein, bcl-2, and matrix metalloproteinases, counts of argyrophilic nucleolar organizer regions and proliferating cell nuclear antigen, and the Ki-67 index [22][23][24][25][26][27][28] have been conducted to predict the biological behavior of thymomas. In the present study, because we found D2-40 immunoreactivity in metastatic tumor cells within the lymph nodes, we hypothesized that podoplanin expression could be a useful marker of more aggressive behavior of thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Tateyama et al (35) reported that all thymic epithelial tumors, including noninvasive thymomas, demonstrated overexpression of p53 protein. Here, overexpression of p53 protein was observed only in Type B3 and C thymomas, suggesting that overexpression of p53 protein may be useful as a marker for these more aggressive subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, CD70 positivity may serve as a marker for thymic carcinoma, and has potential for differentiation of thymic carcinoma from other mediastinal neoplasms, rather than affirmation of a causative pathogenetic relationship between this disease and EBV (26). Other surface antigenic molecules have shown aber- Thymic carcinoma has been associated with increased expression of epithelial membrane antigen, cytokeratin subtypes, and p53 protein (32)(33)(34)(35)(36)(37). The p53 protein is positive in about three quarters (14 of 19) of thymic carcinoma patients (37).…”
Section: Molecular Pathologymentioning
confidence: 99%